2018
DOI: 10.2147/ott.s168861
|View full text |Cite
|
Sign up to set email alerts
|

CEP55 promotes the proliferation, migration and invasion of esophageal squamous cell carcinoma via the PI3K/Akt pathway

Abstract: BackgroundCentrosomal protein 55 (CEP55) is an important prognostic biomarker that plays an essential role in the proliferation, migration and invasion of multiple tumors. We aimed to investigate the prognostic value of CEP55 in pN0 esophageal squamous cell carcinoma (ESCC) and explore its biological function in ESCC cells.MethodsWe used immunohistochemistry and Western blot analysis to detect the expression of CEP55 in ESCC. Furthermore, both in vitro and in vivo assays were used to determine the effect of CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…With both AKT2 and KRAS amplification, enhanced alterations involving PI3K/AKT/mTOR signaling have been detected in the genomic profiling of ESCC (31,32). Approximately 90% of tumors exhibit some degree of EMT during tumor development (11); notably, it was herein demonstrated that Rap1A activates AKT signaling to mediate EMT, and is regulated by the transcription factor SP1, which is consistent with the hypothesis that SP1 plays a key role in ESCC (23). Taken together, the findings of the present study combined with those of previous reports further indicated that AKT signaling may be positively regulated by Rap1A in ESCC.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…With both AKT2 and KRAS amplification, enhanced alterations involving PI3K/AKT/mTOR signaling have been detected in the genomic profiling of ESCC (31,32). Approximately 90% of tumors exhibit some degree of EMT during tumor development (11); notably, it was herein demonstrated that Rap1A activates AKT signaling to mediate EMT, and is regulated by the transcription factor SP1, which is consistent with the hypothesis that SP1 plays a key role in ESCC (23). Taken together, the findings of the present study combined with those of previous reports further indicated that AKT signaling may be positively regulated by Rap1A in ESCC.…”
Section: Discussionsupporting
confidence: 87%
“…As the closest relative of Ras, Rap1A was previously shown to regulate MAPK/ERK signaling in solid tumors (17,25,26). In addition to ERK, Rap1A promotes cancer cell proliferation via AKT signaling (27), and AKT activation plays a crucial role in the progression of ESCC, including cancer cell growth, migration, invasion and metastasis (11,(28)(29)(30). With both AKT2 and KRAS amplification, enhanced alterations involving PI3K/AKT/mTOR signaling have been detected in the genomic profiling of ESCC (31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more, PIK3CA mutations are frequent in ESCC associated with chagasic megaesophagus and are associated with a worse patient outcome [99]. HERG1, LSD1, CEP55, CACNA2D3, CircVRK1 and lncRNA GAS5 affect the proliferation, migration, invasion or radioresistance of ESCC cells via the PI3K/AKT pathway [100][101][102][103][104][105]. After all, a limited number of clinical trials of PI3K inhibitors BYL719 and BKM120 in ESCC patients may bring efficacious therapeutic proposals ( Table 2).…”
Section: Deregulation Of the Pi3k/akt Pathway In Digestive System Tumorsmentioning
confidence: 99%
“…In addition, CEP55 is part of a CIN signature of 10 genes whose high expression is associated with drug resistance, CIN and cell proliferation [67]. CEP55, also a potent cancer testes antigen and a key regulator of spermatogenesis [68], has been linked mainly to regulation of the PI3K/AKT pathway and its overexpression is associated with proliferation, invasion, migration and metastasis [66]. CEP55 binds to and stabilizes the catalytic subunit, p110 of PIK3CA and increases AKT signaling, in vitro and in vivo [68,69].…”
Section: Cep55: a Rising Star Of Tumorigenesismentioning
confidence: 99%